Suture technique and material selection in Da Vinci robotic biliary reconstruction surgery - Hao Zou; Chengzhan Zhu; Mengling Ji; Zejiang Xu; Chuandong Sun (Intelligent Surgery, 2022)
Roux-en-Y hepaticojejunostomy is an important component of robotic biliary reconstruction surgery. High-quality hepaticojejunostomy is inseparable from a number of key factors.These factors include the incision of bile duct stump, the handling of the bowel, anastomosis method selection, and selection of anastomotic threads, etc. More attention should be paid to the improvement of biliary reconstruction techniques in the direction of refinement and homogeneity.